PENGARUH KOMUNIKASI DAN KEPERCAYAAN TERHADAP EFEKTIVITAS TIM KELOMPOK KERJA GURU SEKOLAH DASAR KECAMATAN KOJA JAKARTA UTARA - Halimatusha’diah Halimatusha’diah (Universitas Negeri Jakarta, 2013)
The objective of this research is to obtain information concerning to the effect of communication and trust toward the effectiveness of teacher’s teamwork. Data collection done toward 80 from 100 teachers of teacher’s teamwork Dewi Sartika in the district Koja, North Jakarta. The methodologhy of this research used the survey method. Respondents were chosen by simple random sampling technique. The data were collected with questionnaire and analyzed with path analysis. Result of this analysis is concluded that (1) there is the postive direct effect of communication toward team effectiveness, (2) there is positive direct effect of trust toward team effectiveness, and (3) there is positive direct effect of communication toward trust.